The Effect of Giving Warm Water Foot bath Mixed with Salt on Blood Pressure in Elderly People with Hypertension - Palupi, Dwi Lestari Mukti; Ulkhasanah, Muzaroah Ermawati; Widiastuti, Agung; Marni, Marni; Sani, Fakhrudin Nasrul (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The definition of hypertension is an increase in systolic blood pressure greater than 140 mmHg and diastolic blood pressure greater than 90 mmHg when tested twice every minute with sufficient rest time or in a calm state. Pharmacological and non-pharmacological therapy are two elements of hypertension management. Pharmacological therapy often involves antihypertensive drugs, while non-pharmacological therapy includes traditional or complementary alternative medicine. One of them is soaking feet using salt. The purpose of this study was to determine the effect of soaking feet using salt water in lowering blood pressure values. Methods: This is an experimental study with a one group preposttest design. Results: The average value of the respondent's blood pressure before the intervention was around 160/100 mmHg, after the intervention the blood pressure value decreased on average around 145/90 mmHg. Conclusion: Soaking feet in salt water has a large impact on blood pressure before and after the intervention is given, with a p value of 0.000.